The Role of Information Technology in Advancing Public Service Systems for Society 5.0 and Smart Cities in Yemen - Salah Abdullah Khalil Abdulrahman; Anik Nur Handayani (Universitas Ngeri Malang, 2022)
Smart cities and society 5.0 are two concepts that work well together since they both call for intelligent people who have achieved society 5.0 level. as well as technologically advanced environs. One of the essential components of developing a smart city and the Yemeni society 5.0 is ensuring the efficient operation of an information system. Smart city development in Yemeni is hampered by numerous problems. These problems include the city government's slow response time to citizen complaints, its lack of transparency when administering the city, the lack of infrastructure for a successful information exchange between the community and the government, and the human resources department's lack of digital literacy. This study aims to provide a broad overview of the public service system that might be applied to the development of an Yemeni smart cities utilizing the idea of a society 5.0. The study's findings show an improved, integrated public service system that Yemeni may be able to embrace. The study's conclusions are based on issues, data analysis results, and Yemeni’s requirements for requesting public services. Under the adjusted strategy, Yemeni 's urban development problems should be gradually and equally addressed, moving the country toward a smart city. Kota pintar dan masyarakat 5.0 adalah dua konsep yang bekerja sama dengan baik karena keduanya membutuhkan orang-orang cerdas yang telah mencapai tingkat masyarakat 5.0. serta lingkungan yang berteknologi maju. Salah satu komponen penting dalam mengembangkan kota pintar dan masyarakat Yaman 5.0 adalah memastikan pengoperasian sistem informasi yang efisien. Pengembangan kota pintar di Yaman terhambat oleh berbagai masalah. Masalah-masalah ini termasuk lambatnya waktu respons pemerintah kota terhadap keluhan warga, kurangnya transparansi dalam mengelola kota, kurangnya infrastruktur untuk pertukaran informasi yang sukses antara masyarakat dan pemerintah, dan kurangnya literasi digital departemen sumber daya manusia. Penelitian ini bertujuan untuk memberikan gambaran luas tentang sistem pelayanan publik yang mungkin dapat diterapkan pada pengembangan kota pintar Yaman dengan memanfaatkan gagasan masyarakat 5.0. Temuan penelitian ini menunjukkan sistem pelayanan publik yang lebih baik dan terintegrasi yang mungkin dapat dianut oleh orang Yaman. Kesimpulan studi didasarkan pada isu, hasil analisis data, dan persyaratan Yaman untuk meminta layanan publik. Di bawah strategi yang disesuaikan, masalah pembangunan perkotaan Yaman harus ditangani secara bertahap dan merata, menggerakkan negara menuju kota pintar.